The spectacle of intimacy : a public life for the Victorian family - Chase, Karen, 1952- (Literature in history (Princeton, N.J.), 2000)
Love of home life, the intimate moments a family peacefully enjoyed in seclusion, had long been considered a hallmark of English character even before the Victorian era. But the Victorians attached unprecedented importance to domesticity, romanticizing the family in every medium from novels to government reports, to the point where actual families felt anxious and the public developed a fierce appetite for scandal. Here Karen Chase and Michael Levenson explore how intimacy became a spectacle and how this paradox energized Victorian culture between 1835 and 1865. They tell a story of a society continually perfecting the forms of private pleasure and yet forever finding its secrets exposed to view. The friction between the two conditions sparks insightful discussions of authority and sentiment, empire and middle-class politics. --From publisher's description.